PENILAIAN BERBASIS KELAS - Tatu Hilaliyah (Jurnal Membaca Bahasa dan Sastra Indonesia, 2018)
Class-Based Assessment is a process of class-based assessment, which is the process of collecting, reporting, and using information about student learning outcomes by applying the principles of continuous, authentic, accurate, and consistent assessment of learning activities under the authority of teachers in the classroom. As well as activities undertaken to obtain and streamline information about student learning outcomes at the classroom level during and after the learning activities. The classroom-based assessment aims to determine the progress and learning outcomes of learners, diagnose learning difficulties, provide feedback or refinement of learning process, determination of class increase, and motivate student learning by knowing and understanding themselves and stimulate to make improvement efforts.